Three-dimensional MoSx (1 < x < 2) nanosheets decorated graphene aerogel for lithium–oxygen batteries. Issue 28 (30th June 2016) - Li, Liangyu; Chen, Chunguang; Su, Junming; Kuang, Peng; Zhang, Congcong; Yao, Yu; Huang, Tao; Yu, Aishui
Abstract : MoS x /graphene aerogels with a 3D architecture were synthesized using a hydrothermal and freeze-drying method and were further applied in Li–O2 batteries as a potential oxygen cathode. Abstract : The electrochemical performance of lithium–oxygen (Li–O2 ) batteries depends largely on the architecture and catalytic effectiveness of the oxygen cathode. Herein, in this study, a graphene aerogel decorated with MoS x nanosheets (MoS x /HRG) with a three-dimensional porous framework synthesized using a one-step hydrothermal reaction followed by freeze-drying is reported. The MoS x /HRG aerogel possesses hierarchical mesopores and micropores, which could facilitate electrolyte impregnation and oxygen diffusion, and provide much more accommodation space for the reaction products. The lithium–oxygen batteries based on this MoS x /HRG aerogel cathode show improved electrochemical performance, with a high initial discharge capacity up to 6678.4 mA h g −1 at a current density of 0.05 mA cm −2 and better cycling capability with a cut-off capacity of 500 mA h g −1 at a current density of 0.1 mA cm −2, compared with the lithium–oxygen batteries based on an HRG aerogel cathode. The enhanced performance is ascribed to the excellent catalytic activity of the MoS x nanosheets and the unique three-dimensional porous architecture.